GFRα 1-2-3-4 co-receptors for RET Are co-expressed in Pituitary Stem Cells but Individually Retained in Some Adenopituitary Cells - Pradilla Dieste, Alberto; Chenlo, Miguel; Perez-Romero, Sihara; Garcia-Rendueles, Ángela R.; Suarez-Fariña, Maria; Garcia-Lavandeira, Montserrat; Bernabeu, Ignacio; Cameselle-Teijeiro, José Manuel; Alvarez, Clara V. (Frontiers in Endocrinology, 2020)
The RET tyrosine kinase receptor is expressed by the endocrine somatotroph cells of the pituitary where it has important functions regulating survival / apoptosis. However, RET is also expressed by the GPS pituitary stem cells localized in a niche between the adenopituitary and the intermediate lobe. To bind any of its four ligands, RET needs one of four co-receptors called GFR1-4. It has been previously shown that GFR1 is expressed by somatotroph cells and acromegaly tumours. GFR2 was shown to be expressed by pituitary stem cells. GFR4 was proposed as not expressed in the pituitary. Here we study the RNA and protein expression of the four GFR co-receptors for RET in rat and human pituitary. The four co-receptors were abundantly expressed at the RNA level both in rat and human pituitary, although GFR4 was the less abundant. Multiple immunofluorescence for each co-receptor and -catenin, a marker of stem cell niche was performed. The four GFR co-receptors were co-expressed by the GPS cells at the niche colocalizing with -catenin. Isolated individual scattered cells positive for one or other receptor could be found through the adenopituitary with low -catenin expression. Some of them co-express GFR1 and PIT1. Immunohistochemistry in normal human pituitary confirmed the data. Our data suggest that the redundancy of GFR co-expression is a self-supportive mechanism which ensures niche maintenance and proper differentiation.